2013
DOI: 10.3109/08977194.2013.784757
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding epidermal growth factor-like growth factor protects rat intestine after portal triad clamping

Abstract: Heparin-binding epidermal growth factor-like growth factor (HB-EGF) is a potent mitogen and chemotactic factor. HB-EGF attenuates intestinal ischemia/reperfusion injury caused by superior mesenteric artery occlusion. We examined whether HB-EGF offers protection against intestinal congestion/reperfusion (C/R) injury, which is caused by portal triad clamping. Male Sprague-Dawley rats were randomly divided into three equally sized groups: I, sham-operated; II, portal triad clamping (Pringle maneuver); III, II + i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…Frontiers in Physiology frontiersin.org level, and apoptosis index in mice (Liao et al, 2013), suggesting that HB-EGF may protect against intestinal inflammatory diseases, which is also consistent with our results. Therefore, we speculate that HB-EFG was negatively associated with constipation because it is a protective factor for IBD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Frontiers in Physiology frontiersin.org level, and apoptosis index in mice (Liao et al, 2013), suggesting that HB-EGF may protect against intestinal inflammatory diseases, which is also consistent with our results. Therefore, we speculate that HB-EFG was negatively associated with constipation because it is a protective factor for IBD.…”
Section: Discussionsupporting
confidence: 91%
“… Zhou et al (2022) found that HB-EGF significantly reduces TNF-induced intestinal epithelial cell death in vitro and also synergizes with ErbB1 signaling to prevent cell death ( Zhou et al, 2022 ). In addition, an animal experiment using HB-EGF confirmed that intraluminal HB-EGF injection significantly reduces intestinal tissue damage, pro-inflammatory cytokine expression, myeloperoxidase activity, malondialdehyde level, and apoptosis index in mice ( Liao et al, 2013 ), suggesting that HB-EGF may protect against intestinal inflammatory diseases, which is also consistent with our results. Therefore, we speculate that HB-EFG was negatively associated with constipation because it is a protective factor for IBD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation